Pengaruh Edukasi Pertolongan Pertama Tersedak Terhadap Pengetahuan Masyarakat Dikelurahan Tumumpa 1 Kota Manado - Sinta Yunita; Suwandi I. Luneto; Rahmat Hidayat Djalil (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Choking is an emergency condition that must be treated quickly, i fit takes too long it will result in a lack of oxygen and result in death duet o blockage of the respiratory tract by foreign objects in the from of food, toys, etc. The aim of this research was to determine the effect of choking first aid education on community knowledge in the Tumumpa 1 subdistrict, Manado City. The research was conducted using a quasi-experimental research method (one-group prepost test design). The sample in this study wa 12 respondents taken using purposive sampling, research instruments using SAP, Leaflets and Questionnaires. Next, the data that has been collected is processed using the SPSS version 24 computer program to be analyzed using the Mc nonparametric test. Nemar with a significance level (α) 0.05. The results of this research show that there is an influence of first aid choking education on the leve of public knowledge by obtaining a value of p = 0.016, which is 0.016 which is smaller than the value of a ≤ 0.05. This, it can be said that Ha is accepted and H0 is rejected andi t can be concluded that Ha has an effect. Choking first aid education on community knowledge in Tumumpa 1 Subdistrict, Manado City The conclusion is this research is that there is an influence of first aid choking education on community knowledge in Tumumpa 1 Village, Manado City. I tis hoped that this suggestion will add insight and useful knowledge regarding fist aid for choking